Dynamic failure of un-strengthened aluminosilicate glass. (December 2019) - Sheikh, Muhammad Zakir; Zhen, Wang; Tao, Suo; Yulong, Li; Fenghua, Zhou; Majeed, Arfan; Muzamil, Muhammad; Dar, Uzair Ahmed; Gao, Guozhong
Highlights: The tests at static and dynamic loading showed that the ALS glass compressive strength is rate sensitive. The strain history was recorded successfully for both static and dynamic tests from the gauges pasted on specimens. The stress-strain results will be useful in developing a constitutive model for numerical simulations. High-speed images and associated stress-time curve. The overall failure of glass at dynamic loading is because of the axial splitting phenomenon. The macroscopic axial cracks traveled at the speed of 800 m per seconds. Abstract: The dynamic failure of un-strengthened aluminosilicate (ALS) glass in compression and tension is explored employing the modified Split Hopkinson Pressure Bar (SHPB) system and a high-speed camera. The tensile tests are conducted on cylindrical specimens to obtain the tensile strength in glass specimens based on Brazilian testing technique in which cylindrical specimens are compressed diametrically to cause failure in the center of the specimen as a result of tensile stress. Both compression and tensile experiments on ALS glass samples are completed at the range of strain-rate 10 - 4 to 10 2 s - 1 . The compression and tensile experimental results revealed that un-strengthened ALS glass is rate sensitive in relation to their compressive and tensile strength. In dynamic experiments, the glass samples failure process is examined using a high-speed camera and the failure progression in ALS glass is elucidated with the accompanying stress history. The triggering of a crack, growth and glass recovered fragments/pieces are deliberated to enlighten the failure process of glass samples. Test data exhibited that the axial splitting caused the rupture of the glass samples in compression loading. However, in tensile tests, the specimens are failed because of a dominant center crack in the direction of loading. From both static and dynamic compression and tensile experiments, post-tests debris are collected to show the effect of the loading rate. Lastly, the collected glass frags/debris from tensile tests are visualized through a scan electron microscope (SEM) to explain the brittle fracture surfaces.